Rush - Morgan, Peter, 1963-; Howard, Ron, 1954-; Eaton, Andrew; Fellner, Eric; Oliver, Brian, 1971-; Grazer, Brian, 1953-; Hemsworth, Chris; Bruhl, Daniel, 1978-; Wilde, Olivia; Favino, Pierfrancesco; Lara, Alexandra Maria, 1978-; Zimmer, Hans; et al. (Universal City, CA : Universal Studios Home Entertainment, 2014)
Set against the golden age of Formula One racing in the 1970s, Rush is based on the true story of a spectacular sporting rivalry between English playboy James Hunt, and his structured, intelligent opponent, Austrian driver Niki Lauda.
DVD release of the 2013 motion picture.
Special features: Deleted scenes ; Ron Howard: a director's approach.
Music by Hans Zimmer ; editors, Dan Hanley, Mike Hill ; director of photography, Anthony Dod Mantle.
Chris Hemsworth, Daniel Bruhl, Olivia Wilde, Pierfrancesco Favino, Alexandra Maria Lara.
MPAA rating: R; for sexual content, nudity, language, some disturbing images and brief drug use.
DVD, NTSC, region 1 ; anamorphic widescreen (2.40:1) presentation ; Dolby digital 5.1 surround (English and Spanish) and 2.0 stereo. surround (English DVS).
Keywords: Hunt, James, -- 1947-1993 -- Drama; Lauda, Niki, -- 1949- -- Drama; Automobile racing drivers -- 20th century -- Drama; Formula One automobiles -- Drama; Nineteen seventies -- Drama; Feature films -- United States; Biographical films; Historical films; Action and adventure films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities